2020
DOI: 10.1136/bmjpo-2019-000607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and consequences of newborns born small for gestational age: a multisite study in Nepal

Abstract: ObjectiveTo identify the prevalence, risk factors and health impacts associated with small for gestational age (SGA) births in Nepal.MethodsA cross-sectional study was conducted in 12 public hospitals in Nepal from 1 July 2017 to 29 August 2018. A total of 60 695 babies delivered in these hospitals during the study period were eligible for inclusion. Clinical information of mothers and newborns was collected by data collectors using a data retrieval form. A semistructured interview was conducted at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
2
11
3
Order By: Relevance
“…This might be because the education level of mothers in our study was higher than that of Italy. Several studies have suggested primiparity as a risk factor for PTB [ 50 ]; however, primiparity was found to be associated with SGA, term-SGA, and LBW in our study. Our findings are consistent with a previous Japanese study, which indicated that the risk of LBW is lower among multiparous women [ 21 ].…”
Section: Discussioncontrasting
confidence: 97%
“…This might be because the education level of mothers in our study was higher than that of Italy. Several studies have suggested primiparity as a risk factor for PTB [ 50 ]; however, primiparity was found to be associated with SGA, term-SGA, and LBW in our study. Our findings are consistent with a previous Japanese study, which indicated that the risk of LBW is lower among multiparous women [ 21 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Thus, highlighting the importance of country-specific curves to be considered in establishing the diagnosis of SGA. The proportion of SGA in male babies in our study was lower than females (17.6% vs 23.6%), as has also been reported by several studies, 11,[14][15][16] unlike Muhihi et al, 17 who reported a higher risk of SGA in male.…”
Section: Prognostic Factorssupporting
confidence: 86%
“…Although the overall prevalence of SGA estimated was 27% of live births, Nepal's reported prevalence was higher (39.3%) than the present study (20.3%). Conversely, data from the WHO Multicountry Survey on Maternal and Newborn (2010‐2011) 10 and a recent (2017‐2018) multisite study in 12 different hospitals 11 reported a lower prevalence of SGA in Nepal (17.9% and 11.9%, respectively). The decreasing trends in the prevalence of SGA in Nepal could be due to advancement in Nepal's medical sector in the recent years with improvement in mothers' education, higher socioeconomic status, and a better understanding of the importance of antenatal visits during pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…. In low-income countries, severe anaemia along with small for gestational age (SGA) babies are basic reasons for low birth weight outcome ( Paudel, 2020 ). SGA is defined as the weight of the newborn is <10th percentile, or newborn is smaller than the normal of that gestational age ( Col Madendag et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%